2010
DOI: 10.1104/pp.110.160697
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Analysis of the Abscission-Related Transcriptome in the Tomato Flower Abscission Zone in Response to Auxin Depletion

Abstract: The abscission process is initiated by changes in the auxin gradient across the abscission zone (AZ) and is triggered by ethylene. Although changes in gene expression have been correlated with the ethylene-mediated execution of abscission, there is almost no information on the molecular and biochemical basis of the increased AZ sensitivity to ethylene. We examined transcriptome changes in the tomato (Solanum lycopersicum 'Shiran 1335') flower AZ during the rapid acquisition of ethylene sensitivity following fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

46
351
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(407 citation statements)
references
References 117 publications
(157 reference statements)
46
351
2
8
Order By: Relevance
“…Its ultrastructure is characterized by electronlucent ameboidal-shaped nuclei, a well developed Golgi apparatus and endoplasmic reticulum connected with an elaborate plasmodesmal system, pronounced membrane invaginations, and multivesicular and paramural bodies. In addition, polygalacturonases -enzymes involved in the execution of cell separation 4,18 are also located at the proximal side of the AZ. At the distal side of the AZ programmed cell death occurs.…”
Section: Endoreduplication In the Az Is Predominantly On Its Proximalmentioning
confidence: 99%
See 1 more Smart Citation
“…Its ultrastructure is characterized by electronlucent ameboidal-shaped nuclei, a well developed Golgi apparatus and endoplasmic reticulum connected with an elaborate plasmodesmal system, pronounced membrane invaginations, and multivesicular and paramural bodies. In addition, polygalacturonases -enzymes involved in the execution of cell separation 4,18 are also located at the proximal side of the AZ. At the distal side of the AZ programmed cell death occurs.…”
Section: Endoreduplication In the Az Is Predominantly On Its Proximalmentioning
confidence: 99%
“…In tomato (Solanum lycopersicum) the plant hormones ethylene and auxin play central roles in regulating organ abscission by inducing and inhibiting it, respectively. Deblading of leaves or removal of flowers accelerates the abscission process by reducing the auxin supply, [3][4][5] but the process may be even faster when the plants are additionally exposed to ethylene. We have recently shown that AZs of tomato leaf or flower are structured in an asymmetric manner after abscission is triggered (Fig.…”
mentioning
confidence: 99%
“…When physiological changes such as senescence or maturation occur in organs, abscission is induced through reduction of auxin level and induction of ethylene signaling (Meir et al 2010;Taylor and Whitelaw 2001). Abscission is carried out by activation of cell wall degrading enzymes and remodeling proteins, including β-1,4-glucanase (cellulase; Cel), polygalacturonase (PG), xyloglucan endotransglucosylase/hydrolase (XTH), and expansin (EXP), resulting in breakdown of cell adhesion Lashbrook and Cai 2008;Meir et al 2010;Roberts et al 2002;Tucker et al 2007). These events are well conserved in different types of organs and in divergent plant species.…”
mentioning
confidence: 99%
“…Additionally, it was suggested that an important step in the abscission process is the gain of ethylene sensitivity in the AZ (Meir et al . 2010). After 24 h of ethylene treatment, the fracture in the AZ had already formed in the oldest leaves, and the process gradually spread to the younger leaves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these processes are induced by ethylene (Trobacher 2009; Meir et al . 2010; Chersicola et al . 2017).…”
Section: Introductionmentioning
confidence: 99%